Vertical Design Studio Experience in Interior Architecture Education - Melikoğlu Eke, Armağan Seçil; Yücesan, Ebru; Ozar, Betül; ÖZBEK, DERYA ADIGÜZEL (My University, 2018)
Design studios are at the core of interior architecture education. Environments where “learners form their own learning” enhance the communication between the teacherlearner, and learner–learner. Within this scope, the organization of design studios and the models that are applied are still the crucial research subjects on which teaching interior architecture works on. This paper investigates into the vertical interior design studio experience that is rebuilt in accordance with contemporary approaches towards studio education. Vertical interior design studio experience is built on associations, separations and on the interrelations between these associations and separations. The other input of this formation is the relations, associations, separations among the students within the group. The vertical studio setup that is applied during the 2016- 2017 Fall Semester at Department of Interior Architecture and Environmental Design of FMV Işık University is examined in terms of its construction, experience process, outputs and further critical investigation is carried out on the learning method.
Keywords: Interior Architecture Education; Design Studio; Design Process; Vertical Interior Design Studio